Secondary school students and caffeine : consumption habits, motivations and experiences : a thesis presented in partial fulfilment of the requirements of the degree of Master of Science in Nutrition and Dietetics - Turner, Sophie (Massey University, 2019)
Background: Recently, concerns have been raised about adolescent caffeine consumption due to its potentially serious physiological and psychological effects. Adolescents are vulnerable to the effects of caffeine due to their lack of habituation, smaller body mass and changing brain physiology. Increasing independence also exposes adolescents to new caffeinated products and provides greater freedom in their food and beverage decision making. The motivations that drive caffeine intake among adolescents are not well understood, but they are important in order to develop and implement public health strategies to reduce any harmful behavioural patterns and potential adverse effects. Therefore, it is important to determine which groups of adolescents if any are at increased at risk of caffeine-related harm, particularly as previous studies investigating adolescent caffeine intake are limited and outdated, especially within the New Zealand context. Aim: The aim of this study is to explore the caffeine consumption habits of New Zealand adolescents 15 to 18 years; the factors that motivate consumption and reasons for avoiding caffeine, over a range of caffeinated products. Methods: A previously validated caffeine consumption questionnaire (CaffCo) was administered to 217 participants 15 to 18 years via the online survey software Qualtrics. Results: Most (94.9%) New Zealand adolescents consume at least one caffeinated product daily, the most commonly consumed sources being chocolate, coffee, tea and kola drinks. The median daily caffeine intake was 68 mg.day⁻¹. Gender and employment status influence the pattern, but not overall amount of caffeine consumed. Energy drink consumption has risen dramatically over the past decade. One fifth (21.2%) of adolescents consume above the European Food Safety Authority (EFSA) safe level for caffeine intake of 3 mg.kg.⁻¹day⁻¹. Taste, energy and cold temperature were the main motivators for adolescent caffeine consumption. Increased energy, feeling excited, restlessness and sleep disturbances were frequently reported effects following caffeine consumption. Conclusions: This study gives an updated and more detailed view of caffeinated product consumption among New Zealand adolescents. A subset of adolescents consumes caffeine above the EFSA safe level and may benefit from public health strategies to reduce caffeine-related harm. Potential strategies may include education to improve “caffeine literacy” and improved regulations for labelling and advertising.
Keywords: Caffeine habit; New Zealand; Caffeine; Health aspects; Teenagers; Nutrition; Attitudes; adolescents; energy drinks; adverse effect